Administration of depot GnRH agonist prior to programmed frozen-thawed embryo transfer does not improve the live birth rate in ovulatory women: A large, multi-center retrospective study. Issue 40 (7th October 2022) - Wu, Hongbo; Wei, Fu; Tan, Weihong; Dong, Mei; Tan, Ying; Zhang, Xiqian; Song, Ge; Liu, Liling
Abstract : Despite that gonadotropin-releasing hormone (GnRH) agonist pretreatment has been widely used before programmed frozen-thawed transfer (FET), its impact on live birth rates in ovulatory women remains uncertain. In the present study, we aim to determine if GnRH agonists pretreatment before FET improves live birth rates in women undergoing in vitro fertilization with FET. Programmed FET cycles conducted in four infertility centers were retrospectively collected and reviewed for eligibility from January 2016 and December 2017. Patient's demographics, ovarian stimulation parameters, and pregnancy outcomes were compared between those given GnRH agonist pretreatment versus no pretreatment in ovulatory women undergoing FET cycles. A total of 6397 programmed cycles were screened for eligibility, of which 5049 cycles were included in the study for analysis. Compared with the group of no GnRH agonist pretreatment (n = 4143), women in the GnRH agonist group (n = 906) were older (33.0 vs 34.0, P  < .001), had a higher proportion of subjects with previous transfer attempts and had a higher number of embryos transferred. After controlling for confounders, the logistic regression results showed that GnRH agonist pretreatment did not increase the odds of both clinical pregnancy (OR 0.92, 95% CI [0.70–1.20]), ongoing pregnancy (OR 0.91, 95% CI [0.69–1.19]) and live birth rates (OR 0.84, 95% CI [0.64–1.10]). However, when restricted to women who had no previous transfer attempts, women in the GnRH pretreatment group had lower odds of achieving live birth (OR 0.49, 95% CI [0.30–0.79]). Sensitivity analysis performed in patients with male factor infertility causes showed GnRH agonist pretreated group had lower live birth rates compared to no GnRH agonist pretreatment group (OR = 0.65, 95% CI [0.43–0.97]). Our findings suggested that GnRH agonist pretreatment does not bring additional benefits in live birth rate improvements for ovulatory women undergoing FET cycles. Therefore, the pros of using GnRH agonist to reduce premature ovulation should be weighed against the cons of prolonged time to pregnancy, discomforts resulting from pituitary suppression, and increased medical costs associated with GnRH agonist use.